The role of self-efficacy, social and economic support on the quality of life of cancer patients undergoing chemotherapy: A systematic review - Maria Evarista Sugo; Yati Afiyanti; Allenidekania Allenidekania; Dewi Gayatri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Indonesia is currently facing a triple disease burden, including a rise in chronic illnesses such as cancer, which significantly impacts patients' quality of life. Chemotherapy affects not only physical health but also psychological, social, and spiritual well-being. Factors such as self-efficacy, social support, and economic status are believed to strongly influence the quality of life among cancer patients undergoing chemotherapy. Purpose: To examine the effects of self-efficacy, social support, and economic conditions on the quality of life of cancer patients receiving chemotherapy. Method: A systematic review was conducted by searching articles published between 2015 and 2025 across PubMed, ScienceDirect, and Scopus using relevant keywords. Studies included randomized controlled trials, cohorts, case-control, and quasi-experimental designs that explored the relationship between the selected variables and patient quality of life. Ten articles met the inclusion criteria and were analyzed. Results: From a total of 453,025 articles identified, only 10 met the eligibility criteria. Findings consistently indicate that higher self-efficacy, strong social support, and stable economic conditions are positively correlated with improved quality of life in cancer patients undergoing chemotherapy. Conclusion: Enhancing self-efficacy, providing adequate social support, and addressing economic challenges can significantly improve cancer patients’ quality of life. A holistic, integrated approach that includes psychosocial and spiritual care is essential. Nurses and healthcare professionals play a crucial role in delivering these interventions, supported by appropriate policies and education to strengthen global cancer care systems.